Substrate selectivity and inhibition of histidine JmjC hydroxylases MINA53 and NO66. - Türkmen, VA; Hintzen, JCJ; Tumber, A; Moesgaard, L; Salah, E; Kongsted, J; Schofield, CJ; Mecinović, J (Royal Society of Chemistry, 2023)
Non-haem Fe(II) and 2-oxoglutarate (2OG) dependent oxygenases catalyse oxidation of multiple proteins in organisms ranging from bacteria to humans. We describe studies on the substrate selectivity and inhibition of the human ribosomal oxygenases (ROX) MINA53 and NO66, members of the JmjC 2OG oxygenase subfamily, which catalyse C-3 hydroxylation of histidine residues in Rpl27a and Rpl8, respectively. Assays with natural and unnatural histidine analogues incorporated into Rpl peptides provide evidence that MINA53 and NO66 have narrow substrate selectivities compared to some other human JmjC hydroxylases, including factor inhibiting HIF and JMJD6. Notably, the results of inhibition assays with Rpl peptides containing histidine analogues with acyclic side chains, including Asn, Gln and homoGln, suggest the activities of MINA53/NO66, and by implication related 2OG dependent protein hydroxylases/demethylases, might be regulated in vivo by competition with non-oxidised proteins/peptides. The inhibition results also provide avenues for development of inhibitors selective for MINA53 and NO66.